The Interferences of Acehnese to Indonesian Used by Shopkeepers in Medan Johor District - Bilqis, Wan Siti; Mayasari, Mayasari (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 30 No 1 (2023): Maret, 2023)
This is a research which discuses interference. Language interference is the language phenomenon common in bilingual speakers. It is one of bilingualism aspects that occurs on the level of structure and cultural sense whether oral or written, especially when somebody is learning his or her second language. The main problem in this research is what kind of interference is found in shopkeepers and how is the form of interference from Acehnese language to Indonesian in several shops in Medan Johor district. Interference refers to a deviation in using a language by including another language system. The method used is descriptive qualitative which describes a situation in the form of words that are analyzed orally and writing and consider the opinions of other people called sources. As the result of the research, it can be concluded that the interference of the Acehnese language to Indonesian speech that occurs in the conversations of buying and selling transactions in several stores in the Medan Johor district includes morphological interference, and syntactic interference. Factors that cause Aceh language interference to Indonesian speech in Medan Johor District, especially in some traders include intralinguistic is related to the language itself while extralinguistics includes individual factors and socio-cultural factors.